Design of highly potent urea-based, exosite-binding inhibitors selective for glutamate carboxypeptidase II - Tykvart, Jan; Schimer, Jiří; Jančařík, Andrej; Bařinková, Jitka; Navrátil, Václav; Starková, Jana; Šrámková, Karolína; Konvalinka, Jan; Majer, Pavel; Šácha, Pavel (Journal of medicinal chemistry, 2015)
We present here a structure-aided design of inhibitors targeting the active site as well as exosites of glutamate carboxypeptidase II (GCPII), a prostate cancer marker, preparing potent and selective inhibitors that are more than 1000-fold more active toward GCPII than its closest human homologue, glutamate carboxypeptidase III (GCPIII). Additionally, we demonstrate that the prepared inhibitor conjugate can be used for sensitive and selective imaging of GCPII in mammalian cells.
Keywords: Glutamate Carboxypeptidase II; HEK293 Cells; Chemistry Techniques, Synthetic; glutamátkarboxypeptidasa II; Protein Conformation; preklinické hodnocení léčiv; HEK293 buňky; racionální návrh léčiv; vztahy mezi strukturou a aktivitou; Humans; Binding Sites; Molecular Structure; techniky syntetické chemie; Drug Evaluation, Preclinical; molekulární struktura; močovina; Urea; Drug Design; Structure-Activity Relationship; vazebná místa; Enzyme Inhibitors; lidé; konformace proteinů; inhibitory enzymů